Teknik Penerjemahan pada Lirik Lagu “Nemen” Karya Gilga Sahid - Aureola Pribalisty, Nesa; Ananta Helmalia Putri, Tiara; Eka Rahman , Zakyah; Kusumastuti, Fenty (Universitas Tidar, 2025)
This study examines the process of translating song lyrics from Javanese to Indonesian, focusing on the translation techniques used by Mad Lyric, a popular YouTube channel known for its song translations. The increasing popularity of Javanese songs plays a significant role in preserving cultural heritage, but translating song lyrics poses challenges in maintaining the authenticity of meaning and linguistic style. The aim of this study is to identify the translation techniques applied by Mad Lyric and to understand how they preserve meaning and style in the translated lyrics. A descriptive qualitative approach with content analysis was used, focusing on the lyrics translated by Mad Lyric on their YouTube channel. The data were analyzed based on translation techniques, such as literal translation, reduction, amplification, and modulation. The results show that Mad Lyric prioritizes maintaining the original message while adapting it into a more natural and easily understandable style in Indonesian. Modulation and amplification techniques were more dominant in preserving the original nuance of the lyrics while adjusting expressions to the target language. These findings highlight the importance of understa nding cultural and linguistic contexts in music translation, which ultimately enhances the quality of interlanguage translation while preserving the essence of the original message.